Quantum node portal- Devices and information management - Lopez, Sujane Natasha (2017)
An Internship in a European Company for developing a Web application-Domatica Global Solutions, Lisbon was undertaken to complete the Master’s Degree of Computer Engineering-Mobile Computing in the Polytechnic Institute of Leiria. The team Domatica deals with providing IoT solutions used for monitoring, controlling and collecting the data from the IoT gateways. The present work aims to develop a Web application for client’s side. The Web application named Quantum Node Portal is developed for the Devices and Information management. It provides access to the clients to their IoT gateways. Clients can monitor their devices, get various information, also can access the Portal for claiming their IoT gateways. The present work was developed using various technologies such as PHP framework named Laravel and several languages.